A carnavalização e o grotesco pelo prisma do cinema brasileiro contemporâneo - Guerreiro, Alexandre Silva (2008)
The present work is a reflection concerning the contemporary Brazilian cinema under the prism of the theoretical repertoire of the russian Mikhail Bakhtin with an especial focus in two concept-key: the carnivalization and the grotesque. We intend to approach these two concepts and to try its applicability in the panorama of the Brazilian and international cinema, and more deeply in a shortfilm, Vereda Tropical, de Joaquim Pedro de Andrade, and in three features: A Marvada Carne, directed by André Klotzel, Carlota Joaquina, princesa do Brasil, directed by Carla Camurati, and Amelia, directed by Ana Carolina.